Deteksi Daging Babi pada Sampel Bakso Menggunakan Metode Near Infra Red (NIR) dan Kemometrik sebagai Verifikasi Kehalalan (Detection of Pork in Beef Meatball Sample using Near Infra Red and Chemometrics as Halal Verification) - Khrisna Agung Cendekiawan; Bambang Kuswandi; Nia Kristiningrum (Pustaka Kesehatan, 2015)
Meatball (bakso) is one of the favorite foods in Indonesia. The adulteration of pork in beef meatball occurs frequently. This study was aimed to develop a fast and non destructive technique for the detection and classiﬁcation of pork in beef meatball using Near infrared (NIR) spectroscopy, combined with chemometrics, e.g. partial least square (PLS) and linear discriminant analysis (LDA). The spectral bands associated with pork protein (PP), beef protein (BP), and their mixtures in meatball formulation were scanned, interpreted, and identiﬁed by relating them to those spectroscopically representative to pure PF and BF. Study was done in four phases successively; (1) preparation of trained sample; (2) analysis of meatball powder by NIR Spectrophotometer. NIR spectrum were used to form three data sets, i.e. (a) spectrum in full region, (b) spectrum with first derivative, and (c) spectrum with second derivative; then (3) classification model of chemometrics to PLS and LDA was formed using the Unscrambler X 10.2 Software. (4) the NIR method and the best model of chemometric were applied in meatball samples for the prediction in compared with Xematest Pork result. Then prediction from Xematest Pork compared with The result from NIR-Chemometric. Xematest Pork is simillar with the result of NIR-Chemometric. Keywords: beef meatball, pork, adulteration, NIR, LDA.